SFM Fetal Therapy Practice Guidelines: Fetoscopic Laser Photocoagulation in Monochorionic Twins - Dadhwal, Vatsla; Manikandan, Krishnan; Rana, Anubhuti (Journal of Fetal Medicine, 2023)
Fetoscopic laser coagulation is offered as a method of treatment for twin-to-twin transfusion syndrome or twin anemia polycythemia sequence. It involves laser ablation of intercommunicating superficial blood vessels on the surface of the placenta, under sono-endoscopic control. Preterm labor and preterm prelabor rupture of the membranes are known complications. The results depend on the expertise of the surgeon, location of the placenta, indication for treatment, severity of disease, and growth of babies. The chances of both babies surviving are around 65% and one baby surviving is 85%.
Keywords: laser; monochorionic twin; twin-to-twin transfusion syndrome